Asymmetry in the Cytoarchitecture of the Area 44 Homolog of the Brain of the Chimpanzee Pan troglodytes - Graïc, Jean-Marie; Peruffo, Antonella; Corain, Livio; Centelleghe, Cinzia; Granato, Alberto; Zanellato, Emanuela; Cozzi, Bruno (Frontiers in Neuroanatomy, 2020)
The evolution of the brain in apes and man followed a joint pathway stemming from common ancestors 5–10 million years ago. However, although apparently sharing similar organization and neurochemical properties, association areas of the isocortex remain one of the cornerstones of what sets humans aside from other primates. Brodmann’s area 44, the area of Broca, is known for its implication in speech, and thus indirectly is a key mark of human uniqueness. This latero-caudal part of the frontal lobe shows a marked functional asymmetry in humans, and takes part in other complex functions, including learning and imitation, tool use, music and contains the mirror neuron system (MNS). Since the main features in the cytoarchitecture of Broca’s area remains relatively constant in hominids, including in our closest relative, the chimpanzee Pan troglodytes, investigations on the finer structure, cellular organization, connectivity and eventual asymmetry of area 44 have a direct bearing on the understanding of the neural mechanisms at the base of our language. The semi-automated image analysis technology that we employed in the current study showed that the structure of the cortical layers of the chimpanzee contains elements of asymmetry that are discussed in relation to the corresponding human areas and the putative resulting disparity of function.